Variable response to propranolol therapy for infantile hemangiomas - Vishesh Jain; Subhasis Roychoudhury; Rajiv Chadha; Archana Puri (Wolters Kluwer Medknow Publications, 2012)
Since propranolol was accidentally discovered to induce involution of hemangiomas, it is being used by many clinicians with a favourable response. We present our experience with use of propranolol and report three infants with hemangiomas who were treated with propranolol. First infant had a marked involution of the lesion; second infant had a appreciable response while the third infant had a initial minimal response with progressive increase in size of the lesion.